Health care for the obese person in the Intensive Care Unit (ICU) - dos Santos, Jéssica Batista; Andrade, Vandelene Mota; Sagrillo, Cristiano Pereira; Braga , Daniella da Silva; da Costa , Melina Even Silva; Freire, Gabriel Henrique Ellwanger; Gonçalves , Caroline Ruas; Lopes, Carlos Eduardo de Araujo; da Silva , Natalia Rodrigues; Cabeça Filho, Gilberto Cesar Macedo (Seven Editora, 2023)
Research Question: What is the Hearth care for obese people in the Intensive Care Unit (ICU)? General and specific objective respectively: To analyze what are the causes and consequences of obesity; To investigate what are the public policies to combat obesity; To identify in the literature which are the health care to be applied in the care of the obese person. Hypothesis: Health care directed to the treatment of obese people in the Intensive Care Unit contributes to the improvement of their clinical condition. Type of study: Narrative review. DOI: https://doi.org/10.56238/colleinternhealthscienv1-132